INFLUENCE OF REFORM IN THE SECTOR OF TOURISM ON THE GROWTH OF THE ECONOMY OF UZBEKISTAN AND DEVELOPMENT OF ENTREPRENEURSHIP - Urkinbaev Takhir Abdukarimovich (Labor economics and human capital, 2024)
This article highlights the importance of tourism in the economy of Uzbekistan. The problems of transforming tourism into a highly profitable sector of the economy, as well as the legal framework and opportunities for the development of tourism are also discussed. Recommendations have also been developed for the development of great tourism potential and competitive tourism offers and for the development of entrepreneurship. Particular attention is paid to the tourism opportunities and potential of the republic, as well as the development of infrastructure and the development of necessary measures to improve the small business system.